Differentiation with User-Generated Content - Zhang, Kaifu; Sarvary, Miklos (Management Science, 2015)
This paper studies competition between firms whose “products” (content) are generated by their customers (users). Video sharing sites, social networks, online games, etc. all rely heavily on user-generated content and have been growing significantly in the last decade. We model a Hotelling style market in which consumers have heterogeneous tastes along a circular city. In a first step, we consider two ex ante identical firms whose offerings entirely depend on user-generated content. Consumers contribute content to the firm they join and benefit from the content provided by the others, their valuation being higher the closer the content contributor is to the content consumer (i.e., there are local network effects). In such a setting, we show that ex ante identical firms can acquire differentiated market positions that spontaneously emerge from user-generated content. Moreover, such differentiation may take interesting patterns, wherein a firm simultaneously attracts multiple distinct consumer segments that are isolated from each other. Greater segregation, measured by the number of disjoint segments in each platform, reduces consumer valuation for content, but interestingly, it intensifies firm competition. We show that this insight can help us refine the set of possible equilibria. In a second step, we consider firms that explicitly differentiate their offerings by generating some content on their own. We show that user-generated content may strengthen or defeat firms' intended positioning (i.e., firms attract consumers located opposite to their chosen positions) and consumer surplus may be higher in the latter case. Finally, we allow multihoming by consumers and show that the previous equilibrium patterns remain valid, but in most equilibria, a subset of consumers (located between rival firms' core clienteles) are multihomers. More multihoming consumers imply reduced differentiation and higher degree of platform competition. We relate these findings to anecdotal evidence and explore their strategic implications for competing firms relying on user-generated content. This paper was accepted by J. Miguel Villas-Boas, marketing.